DESIGN THINKING AS A INNOVATION TOOL IN ORGANIZATION (Innovation in Woodworking Industry and Engineering design, 2026)
The popularity of design thinking in the last few years is part of a wider debate about the role of design in business, and its place in business education. The reason for the surge in interest of the ‘methodology’ of design, is because of design potential for enabling business – and cultural – transformation, through the application of design processes to other areas. Many famous brands are experimenting with ways to embed design thinking in their organizational processes, and in using it as a company-wide innovation tool.